Coping With COVID-19: Mindfulness-Based Approaches for Mitigating Mental Health Crisis - Antonova, Elena; Schlosser, Karoly; Pandey, Rakesh; Kumari, Veena (Frontiers in Psychiatry, 2021)
The novel coronavirus disease COVID-19 that first emerged in Wuhan, China, in Nov-Dec 2019 has already impacted a significant proportion of the world population. Governments of many countries imposed quarantines and social distancing measures in 2020, many of which remain in place, to mitigate the spread of the SARS-Cov-2 virus causing the COVID-19 disease. The direct impact of COVID-19 on people infected with the virus, their families and the health care workers, as well as the impact of the mitigation measures such as quarantine, social distancing, and self-isolation on the rest of the population have contributed to a global mental health pandemic, including anxiety, depression, panic attacks, posttraumatic stress symptoms, psychosis, addiction, obsessive-compulsive disorder, and suicidality. These effects are present acutely (for example, due to fear of contamination or losing loved ones, effects of quarantine/isolation, withdrawal of community and social services, etc.) and may continue long after the pandemic is over (for example, due to bereavement, unemployment, financial losses, etc). The COVID-19 pandemic has triggered mental health problems in people without previous history of mental illness, as well as worsened the symptoms in those with pre-existing psychiatric diagnosis. Therefore, the global effort is called for to deal with this mental health pandemic secondary to COVID-19 itself to address the emergence of new as well as the exacerbation of the existing mental health issues. Conversely, this global context provides an extraordinary opportunity for studying individual differences in response to and resilience in the face of physical and psychological threat, challenge to “normal” way of life, and long-term uncertainty. In this viewpoint article we outline the particular suitability of mindfulness, its skills and mechanisms, as an approach to the prevention and management of mental health issues, as well as to the promotion of well-being and building the foundations of adaptability and flexibility in dealing with the long-term uncertainty and profound changes to the social, economic, and possibly political systems as this pandemic continues to unfold.